Caracterização físico-química, teor de antioxidante e perfil sensorial de méis de abelhas submetidos à desumidificação e umidificação - Silva, Mônica Cristina de Paiva (Universidade Federal Rural do Semi-Árido, 2015)
The honey bee is a resulting food processing the nectar of plants by bees, has its composition strongly influenced by the flowering, soil, climate conditions and bee species. Thus, the honey bee Apis mellifera L. species and genus Melipona subnitida, with different characteristics, both sensory and physical-chemical and antioxidants. The Melipona subnitida honey stands out for high water content and therefore technological processes (dehumidification and maturity) are performed to extend its useful life. Otherwise, the humidifying Apis mellifera L. honey can result in a product similar in characteristics to the Melipona honey, but with reduced caloric constituents. Thus, this study aimed to evaluate the physic-chemical characteristics, antioxidant content and sensory profile honeys of Apis mellifera L. and Melipona subnitida submitted humidification and dehumidification treatments. For this, honey samples of Apis mellifera L. and Melipona subnitida were collected in the Rio Grande do Norte state. Honeys packed in sealed containers were transported to the Food Technology Laboratory of the Universidade Federal Rural do Semi-Árido (UFERSA), located in the Center Campus in the Mossoró-RN city, where they were stored by refrigeration (6 °C) until the completion analyzes physicochemical (moisture, pH, free acidity, water activity, reducing sugars, apparent sucrose, diastase activity, electrical conductivity, ash, hydroxymethylfurfural, insoluble solids in water and color), antioxidant (phenolic compounds, flavonoids, antioxidant capacity) and sensory profile (aroma, flavor, fluidity, color, acceptance and purchase intent). For evaluation was used four samples of 1 L of honey for each bee species. The samples were divided into two samples with equal quantities, was evaluated in natura and the other was subjected to dehumidification in air circulating oven at 40 °C and relative humidity 30 % (Melipona subnitida honey), and humidification by adding distilled water (Apis mellifera L. honey). Data were subjected to analysis of variance (p <0.01), the F test. For compare means, t tests were used (p <0.05) for the results of physico-chemical analysis and antioxidants, and Friedman (p <0.05) for the results of the sensory analysis. Treatment dehumidification honeys of Melipona subnitida significantly changed the moisture content, water activity, reducing sugars, sucrose, ash, insoluble solids and color. While the treatment of humidification honeys of Apis mellifera L. changed the moisture content, water activity, reducing sugars, sucrose. As for the content (total phenolics, flavonoids) and antioxidant capacity there were no treatment effects. However, the sensory attributes of aroma, fluidity and color of honey show any differences in the treatments. However, the flavor, acceptance and purchase intent were not affected by honeys treatments of both species
Physicochemical characterization, antioxidant content and sensory profile of honey bee subjected to dehumidification and humidification
Keywords: Capacidade antioxidante; Aroma; Fenólicos; Fluidez; Antioxidant capacity; Aroma; Phenolic; Fluidity; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL